Study of Mechanical Properties for Masonry Produced Using Hemp Shive and Lime in the form of Interlocking Blocks - Sinsiri, Teerawat; Thaiying, Komchai; Phetcharat, Sudniran (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
This objective of this article was to present a production method for masonry that uses hemp shiv, lime and water as the composition for interlocking blocks. The aim was to identify the best condition for substituting lime with hemp shiv as much as possible in order to develop energy efficient construction material. The tests performed included water absorption, dry density test, and compressive test according to the TIS109-2517. Comparisons were made for samples containing hemp at 100, 200, 300, and 400 grams per block or from 2.86 – 26.67 per cent alternative material per block. It was found that the use of lime as the binding material for hemp shiv resulted with interlocking blocks with good physical appearance. However, there are limitations on strength and water absorption properties. All of the conditions tested resulted with a compressive strength of less than 0.5 MPa and the water absorption test was not able to be carried out. The results of this research indicated that for the production of interlocking hempcrete blocks using only lime as the binding material had limitations on its strength and can not be used in construction work. Cement is still required as binding material for this purpose.